Investigation of factors influencing thoroughbred horses' racing career length in Turkey - Özen, D.; Kaya, U.; Özen, H.; Ambarcioglu, P.; Ünal, N.; Gürcan, I. S. (Journal of Equine Veterinary Science, 2021)
The aim of this research was to determine the average length of a Thoroughbred horse's racing career in Turkey using survival functions of Thoroughbred horses with various characteristics. In addition, the aim was to identify risk factors that could influence the duration of a Thoroughbred horse's racing career and develop a survival model that took these factors into account. A total of 11,721 Thoroughbred horses born in 2007 and later were included in the study population. The horses involved in the study were followed for a minimum of 1 year. Kaplan-Meier analysis was used to calculate the average length of racing career for each factor studied. Extended Cox regression analysis was used to determine the risk factors upon time of career ending and to create a survival model. Results showed that, the mean career length of Thoroughbred horses was 17.79 months (95% CI: 17.41-18.13). Also, "starting age of the race," "number of starts," "type of track where the race started," "racing on a single type racetrack" and "earning status" were found risk factors that affect the length of the racing career. Earnings was the top relative contributor to the established model, and its sole adjusted effect showed that being in the lowest earning group increased the hazard of career ending 2.28 times (95% CI:1.98-2.61) compared to horses with highest earning group. In conclusion, clear differences upon the length of racing career was observed for each investigated factor. Future studies should be considerate of these differences when analyzing population data.